Multidrug-resistant bacteria in ICU: fact or myth. Issue 2 (April 2020) - De Waele, Jan J.; Boelens, Jerina; Leroux-Roels, Isabel
Abstract : Purpose of review: Antimicrobial resistance (AMR) is increasing in ICUs around the world, but the prevalence is variable. We will review recent literature and try to answer the question whether this is a myth or a new reality, as well as discuss challenges and potential solutions. Recent findings: AMR is diverse, and currently Gram-negative multidrug-resistant organisms (MDROs) are the main challenge in ICUs worldwide. Geographical variation in prevalence of MDROs is substantial, and local epidemiology should be considered to assess the current threat of AMR. ICU patients are at a high risk of infection with MDRO because often multiple risk factors are present. Solutions should focus on reducing the risk of cross-transmission in the ICU through strict infection prevention and control practices and reducing exposure to antimicrobials as the major contributor to the development of AMR. Summary: AMR is a reality in most ICUs around the world, but the extent of the problem is clearly highly variable. Infection prevention and control as well as appropriate antimicrobial use are the cornerstones to turn the tide.